Structural Basis for Chaperone‐Independent Ubiquitination of Tau Protein by Its E3 Ligase CHIP. Issue 15 (18th February 2022) - Munari, Francesca; Mollica, Luca; Valente, Carlo; Parolini, Francesca; Kachoie, Elham Ataie; Arrigoni, Giorgio; D'Onofrio, Mariapina; Capaldi, Stefano; Assfalg, Michael
Abstract: The multi‐site ubiquitination of Tau protein found in Alzheimer's disease filaments hints at the failed attempt of neurons to remove early toxic species. The ubiquitin‐dependent degradation of Tau is regulated in vivo by the E3 ligase CHIP, a quality controller of the cell proteome dedicated to target misfolded proteins for degradation. In our study, by using site‐resolved NMR, biochemical and computational methods, we elucidate the structural determinants underlying the molecular recognition between the ligase and its intrinsically disordered substrate. We reveal a multi‐domain dynamic interaction that explains how CHIP can direct ubiquitination of Tau at multiple sites even in the absence of chaperones, including its typical partner Hsp70/Hsc70. Our findings thus provide mechanistic insight into the chaperone‐independent engagement of a disordered protein by its E3 ligase. Abstract : An NMR‐based structural investigation of the Tau–CHIP complex revealed a multi‐domain, dynamic interaction that explains the origin of the multiple‐site ubiquitination of Tau operated by CHIP, as well as the ability of this ligase to modify Tau in the absence of chaperones.